2021
DOI: 10.1021/acs.iecr.1c02560
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Upgrading to Renewable Diesel over Nickel Supported on Natural Mordenite Catalysts

Abstract: In the present work the valorization of natural mordenite as a catalyst support was investigated. Natural mordenite of Greek origin was activated by acid treatment with an aqueous solution of HCl. This treatment led to a material with a high specific surface area (156 m2 g–1). Ni catalysts (10 wt % Ni) supported on activated mordenite were synthesized by incipient wetness impregnation (IWI), wet impregnation (WI), infiltration (INF), and deposition–precipitation (DP). They were evaluated for the biodiesel upgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Moreover, the catalytic efficiency obtained in the present study over nickel species supported on post-treated mineral montmorillonite was comparable to those obtained over nickel species supported on synthetic supports, though a rigorous comparison is very difficult to achieve due to the quite different evaluation conditions adopted in each case. Moreover, the comparison of the present results regarding the Mo–Ni bimetallic catalyst with the corresponding catalysts supported on various synthetic supports [ 20 , 21 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] showed that the Mo promoting action was also clearly manifested over nickel catalysts supported on mineral montmorillonite.…”
Section: Resultsmentioning
confidence: 58%
See 4 more Smart Citations
“…Moreover, the catalytic efficiency obtained in the present study over nickel species supported on post-treated mineral montmorillonite was comparable to those obtained over nickel species supported on synthetic supports, though a rigorous comparison is very difficult to achieve due to the quite different evaluation conditions adopted in each case. Moreover, the comparison of the present results regarding the Mo–Ni bimetallic catalyst with the corresponding catalysts supported on various synthetic supports [ 20 , 21 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ] showed that the Mo promoting action was also clearly manifested over nickel catalysts supported on mineral montmorillonite.…”
Section: Resultsmentioning
confidence: 58%
“…Several methodologies have been developed to minimize these problems involving the use of suitable supports, nickel loading, preparation methods and optimized experimental conditions (mainly reaction temperature and hydrogen pressure) [ 11 ], as well as modification of the structure of the supported nickel through development of nickel phosphide [ 44 , 45 , 46 ], nitride [ 47 , 48 ] or carbide catalysts [ 32 , 48 ]. Another very promising prospect for overcoming the above drawbacks and further increasing the efficiency of nickel catalysts is the use of promoters, among which molybdenum oxides are the most effective [ 20 , 21 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. The literature survey indicated that excellent promoting action is observed in molybdenum oxides, mainly for catalysts with a Ni/(Ni+Mo) atomic ratio close to 0.85–0.95 [ 20 , 21 , 49 , 50 , 52 , 55 , 56 , 59 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations